Discursive construction of the ‘scholar' identity: a critical genre analysis of chinese and english academic biographies - Liu, Shuai (Frontiers in Psychology, 2025)
Scholar biographies, though often overlooked, serve as a significant genre for the discursive construction of academic identity. This study adopts a Critical Genre Analysis (CGA) framework to examine how professional identities are constructed in Chinese and English scholar profiles within the field of linguistics. Combining textual analysis with interview data, the research identifies shared rhetorical structures and recurring identity types, alongside notable cross-cultural differences shaped by institutional, and socio-cultural factors. The interviews further reveal how scholars strategically present themselves in response to contextual expectations. By integrating textual and contextual perspectives, the study deepens our understanding of how academic identities are constructed and culturally mediated, offering implications for academic communication and cross-cultural discourse research.